Isolation, structures, bioactivities, application and future prospective for polysaccharides from Tremella aurantialba: A review - Yan, Yonghuan; Wang, Mengtian; Chen, Ning; Wang, Xu; Fu, Chenghao; Li, Yuemin; Gan, Xiaoruo; Lv, Pin; Zhang, Yan (Frontiers in Immunology, 2022)
Since ancient times, Tremella aurantialba has been proposed to have medicinal and food benefits. Modern phytochemistry and pharmacological studies have demonstrated that polysaccharides, the main components from Tremella aurantialba appear to be an all-round talent resisting a variety of chronic inflammatory diseases and protecting against different types of tumors, diabetes and cardiovascular diseases. These health and pharmacological benefits have gained much attention from scholars around the world. Further, more and more methods for polysaccharide extraction, purification, structure identification have been proposed. Significantly, the bioactivity of plant polysaccharides is affected by many factors such as extraction and purification conditions and chemical structure. This paper provides an overview of recent advances in the isolation, structural features and biological effects of polysaccharides derived from Tremella aurantialba, covers recent advances in the field and outlines future research and applications of these polysaccharides.